1996
DOI: 10.1111/j.1432-1033.1996.0297t.x
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Modifications in Human Erythroleukemia K562 Cells During Induction of Programmed Cell Death by Transforming Growth Factor β1 or Cisplatin

Abstract: Transforming growth factor Pl (TGFP1) and cisplatin induce apoptosis (programmed cell death, PCD) in human erythroleukemia K562 cells in an additive manner. After PCD was induced in K.562 cells, analysis of phospholipid composition, fatty acids and cholesterol content in their membranes showed a decrease in phosphatidylethanolamine and an increase in phosphatidylserine, cardiolipin and phosphatidic acid. Moreover, cisplatin but not TGFPl enhanced sphingomyeline levels in apoptotic cells, whereas TGFPl increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 26 publications
1
34
0
Order By: Relevance
“…Cell suspensions (1 ml/test) were incubated for different time intervals, at 37°C, with 100 nM [ 3 H]AEA, and they were washed three times in 2 ml of culture medium containing 1% bovine serum albumin and were finally resuspended in 200 l of phosphate-buffered saline. Membrane lipids were then extracted (31), resuspended in 0.5 ml of methanol, and mixed with 3.5 ml of Sigma-Fluor liquid scintillation mixture for nonaqueous samples (Sigma), and radioactivity was measured in a LKB1214 Rackbeta scintillation counter (Amersham Pharmacia Biotech). To discern noncarrier-mediated from carrier-mediated transport of AEA into cell membranes, control experiments were carried out at 4°C (22).…”
Section: Materials-chemicalsmentioning
confidence: 99%
“…Cell suspensions (1 ml/test) were incubated for different time intervals, at 37°C, with 100 nM [ 3 H]AEA, and they were washed three times in 2 ml of culture medium containing 1% bovine serum albumin and were finally resuspended in 200 l of phosphate-buffered saline. Membrane lipids were then extracted (31), resuspended in 0.5 ml of methanol, and mixed with 3.5 ml of Sigma-Fluor liquid scintillation mixture for nonaqueous samples (Sigma), and radioactivity was measured in a LKB1214 Rackbeta scintillation counter (Amersham Pharmacia Biotech). To discern noncarrier-mediated from carrier-mediated transport of AEA into cell membranes, control experiments were carried out at 4°C (22).…”
Section: Materials-chemicalsmentioning
confidence: 99%
“…Cell suspensions (2 ml/test) were incubated for different time intervals at 37°C with 100 nM [1-14 C]AnNH; then they were washed three times in 2 ml of culture medium containing 1% bovine serum albumin and were finally resuspended in 200 l of phosphate-buffered saline. Membrane lipids were then extracted (28), resuspended in 0.5 ml of methanol, and mixed with 3.5 ml of Sigma-Fluor liquid scintillation mixture for nonaqueous samples (Sigma), and radioactivity was measured in an LKB1214 Rackbeta scintillation counter. To discern non-protein-mediated from protein-mediated transport of AnNH into cell membranes, control experiments were carried out at 4°C (13).…”
Section: Reverse Transcriptase Polymerase Chain Reaction (Rt-pcr) Andmentioning
confidence: 99%
“…We demonstrated that all these hydroperoxy fatty acids are fully capable of eliciting apoptotic bodies formation, both in human erythroleukemia and neuroblastoma cells. 13 The most active compound is that generated by 5-lipoxygenase from arachidonate (5-HPETE), followed by 13-HPOT, 15-HPETE, 9-HPOT, 9-HPOD, 13-HPOD and 12-HPETE. In this context, it should be recalled that mammalian cells can reduce the lipid hydroperoxides (LOOH) to the purportedly less toxic hydroxides (LOH), in a reaction requiring glutathione (GSH) and catalyzed by glutathione peroxidase: 45 …”
Section: Lipoxygenase Involvement In Apoptotic Pathwaysmentioning
confidence: 99%